2000
DOI: 10.1111/j.8755-8920.2000.430201.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin A, Inhibin B and Activin A in Follicular Fluid of Infertile Women with Tubal Damage, Unexplained Infertility and Endometriosis1

Abstract: Follicular fluid concentration of inhibin A is elevated in follicles of women with endometriosis and is positively correlated with follicle maturation. However, we were unable to demonstrate any association between the follicular fluid concentrations of inhibin A, inhibin B, activin A or oestradiol and the quality and fertilisation capacity of oocytes in women with tubal damage, unexplained infertility or endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…However, other studies found no correlation between FF inhibin B level and oocyte quality or fertilizing capacity (46,47). The results of the present study show significant negative correlations between FF inhibin B level and age or total dose of gonadotropin used for COH; however, we did not find any relationship between FF inhibin B level and number of follicles and oocytes retrieved.…”
Section: Figurecontrasting
confidence: 87%
“…However, other studies found no correlation between FF inhibin B level and oocyte quality or fertilizing capacity (46,47). The results of the present study show significant negative correlations between FF inhibin B level and age or total dose of gonadotropin used for COH; however, we did not find any relationship between FF inhibin B level and number of follicles and oocytes retrieved.…”
Section: Figurecontrasting
confidence: 87%
“…A recent interesting metaanalysis [69] including a total of 1423 patients could show five proteomic biomarkers differentially expressed in women with pre-eclampsia (PE) and PCOS when compared with controls: transferrin, fibrinogen a, b and g chain variants, kininogen-1, annexin 2 and peroxiredoxin 2, among 192 proteomic biomarkers cataloged for PE patients. FF inhibin A levels are significantly higher in patients with endometriosis [70].…”
mentioning
confidence: 84%
“…Follicular fluid may also act as a strong buffer of free radicals (25,26). Furthermore, follicular fluid contains many proteins and other factors that may be beneficial to human oocytes, such as transport proteins, intercellular signals, and hormones (23,24,(27)(28)(29)(30)(31)(32). Although some or all of the above factors could have positive effects on oocyte quality, we speculate in this work that one of the fundamental differences between follicular fluid and artificial culture media is the pH of the two fluids.…”
Section: Discussionmentioning
confidence: 81%